PRCnet: An efficient model for automatic detection of brain tumor in MRI images - Ahmeed Suliman Farhan; Muhammad Khalid; Umar Manzoor (PLoS ONE, 2025)
Brain tumors are the most prevalent and life-threatening cancer; an early and accurate diagnosis of brain tumors increases the chances of patient survival and treatment planning. However, manual tumor detection is a complex, cumbersome and time-consuming task and is prone to errors, which relies on the radiologist’s experience. As a result, the development of an accurate and automatic tumor detection system is critical. In this paper, we proposed a new model called Parallel Residual Convolutional Network (PRCnet) model to classify brain tumors from Magnetic Resonance Imaging. The PCRnet model uses several techniques (such as filters of different sizes with parallel layers, connections between layers, batch normalization layer, and ReLU) and dropout layer to overcome the over-fitting problem, for achieving accurate and automatic classification of brain tumors. Our methodology used data augmentation techniques such as rotation, flipping, and scaling. These enhanced the diversity and quantity of the training dataset, contributing significantly to the model’s improved performance. The PRCnet model is trained and tested on two different datasets and obtained an accuracy of 94.77% and 97.1% for dataset A and dataset B, respectively which is way better as compared to the state-of-the-art models. Our PRCnet code publicly available at: https://github.com/Ahmeed-Suliman-Farhan/PRCnet-Model